2017
DOI: 10.1186/s12888-017-1325-z
|View full text |Cite
|
Sign up to set email alerts
|

What is the significance of onconeural antibodies for psychiatric symptomatology? A systematic review

Abstract: BackgroundPatients with intracellular onconeural antibodies may present with neuro-psychiatric syndromes. We aimed to evaluate the evidence for an association between well-characterized onconeural antibodies and psychiatric symptoms in patients with and without paraneoplastic central nervous system syndromes.MethodsEligible studies were selected from 1980 until February 2017 according to standardized review criteria and evaluated using Quality Assessment of Diagnostic Accuracy Studies−2 (QUADAS-2). We included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Although there are associations between psychosis and several classical autoimmune disorders (see above), including neuropsychiatric lupus, the frequency of ANA and thyroid antibodies in the general population precludes their relevance in defining possible AP. Equally, psychotic features are not infrequent in patients with classical paraneoplastic syndromes, but they are seldom isolated and the utility of antibody testing in individuals with isolated psychiatric presentations remains unclear 74,75 .…”
Section: Potential Association With Infections and Systemic Autoimmunitymentioning
confidence: 99%
“…Although there are associations between psychosis and several classical autoimmune disorders (see above), including neuropsychiatric lupus, the frequency of ANA and thyroid antibodies in the general population precludes their relevance in defining possible AP. Equally, psychotic features are not infrequent in patients with classical paraneoplastic syndromes, but they are seldom isolated and the utility of antibody testing in individuals with isolated psychiatric presentations remains unclear 74,75 .…”
Section: Potential Association With Infections and Systemic Autoimmunitymentioning
confidence: 99%
“…SOX1 antibodies have been linked to neoplastic, paraneoplastic, and non-neoplastic conditions with varying degrees of neurological involvement. Onconeural antibodies, specifically anti-Yo and anti-RI, have been found in those with psychiatric disorders [ 16 , 17 ]. These antibodies can also cause neurological damage by showing affinity to various parts of the central nervous system, leading to dysfunction secondary to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Hu and anti-Yo antibodies were shown to induce neuronal and Purkinje-cell death in the hippocampal and cerebellar regions of rats ( 35 37 ). Case reports suggested that anti-Yo and anti-Ri onconeural antibodies may play a role in autoimmune processes in patients with psychiatric disease ( 6 , 38 , 39 ). Only one of our patients was positive for anti-Amp antibody, two patients had borderline result for anti-Rec, and four patients showed a borderline result for anti-Yo, anti-Hu, anti-SOX1, or anti-Tr antibodies.…”
Section: Discussionmentioning
confidence: 99%